Small and Medium Scale Enterprises and Employment Generation in Akwa Ibom State - Udoinyang, Nathan (International Journal of Applied Research and Sustainable Sciences, 2024)
The study examines Small and Medium Scale Enterprises and Employment Generation in Akwa Ibom State. Specifically, the study highlight and demonstrate the importance of SMEs as a tool for employment generation and solution for the problems associated with youth’s unemployment; identify and highlight the challenges faced by entrepreneurs in establishing SMEs; identify and highlight the policies government should put in place to encourage the establishment of more SMEs in Akwa Ibom State. The population of the study consists of all the 11,990 SMEs as recorded by the directorate of SMEs of Akwa Ibom State in 2021. Taro Yamane formulae was applied to arrive at a sample size of 400 SMEs and 400 questionnaires were strategically distributed among the three (3) senatorial districts in Akwa Ibom State. The research questions of the study were analyzed using statistical tools of mean and standard deviation in Statistical Package for Social Sciences (SPSS) with a mean criterion of 3.0. The study finds out that SME is a veritable tool for employment generation and thus solve the problems associated with unemployment in the state, also that high tax/interest rate, erratic power supply, etc are challenges faced by SMEs in Akwa Ibom State. The study further revealed that policies that will reduce tax/interest rate and promote stable power supply etc should be put in place and thus concluded that SMEs sector in Akwa Ibom State will live up to expectation in its core responsibility of employment generation in the state if these policies are enacted